2021
DOI: 10.1016/j.jiac.2021.06.021
|View full text |Cite
|
Sign up to set email alerts
|

The estimated burden of 15 vaccine-preventable diseases from 2008 to 2020 in Japan: A transition by the COVID-19 pandemic

Abstract: Background: Evaluating the national burdens across multiple vaccine-preventable diseases (VPDs) can be informative to identify the areas for improvements in the national immunization program. Methods: The annual burden of diseases from 2008 to 2020 in Japan were calculated with the incidence-and pathogen-based approach for the 15 VPDs (hepatitis B virus infection, human papillomavirus (HPV), influenza, invasive pneumococcal disease, invasive Haemophilus influenzae type b (Hib) disease, invasive meningococcal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Notably, the incidence of varicella, the number of reported cases and public health emergency events in Suzhou in 2020 decreased because of the COVID-19 epidemic. This phenomenon is not an exception and has been observed worldwide in different countries and cites [ 29 , 30 ]. In addition, diseases with a similar mode of transmission to varicella, such as hand, foot, and mouth disease, present varying degrees of decline in reported incidence in 2020 [ 31 ].…”
Section: Discussionmentioning
confidence: 85%
“…Notably, the incidence of varicella, the number of reported cases and public health emergency events in Suzhou in 2020 decreased because of the COVID-19 epidemic. This phenomenon is not an exception and has been observed worldwide in different countries and cites [ 29 , 30 ]. In addition, diseases with a similar mode of transmission to varicella, such as hand, foot, and mouth disease, present varying degrees of decline in reported incidence in 2020 [ 31 ].…”
Section: Discussionmentioning
confidence: 85%
“…In the period between the end of 2019 and the spring of 2022, the COVID-19 pandemic significantly influenced interpersonal contacts, which also have different impacts on measles, mumps and rubella vaccination efforts and burden across the world. For example, Brazil reported a reduction in the number of MMR vaccine doses [ 6 ], while interestingly, Japan reported de-creased estimated annual burdens in 2020 for measles (98%), mumps (47%) and rubella (94%) compared with those in 2019 due to social distances in COVID-19 pandemic [ 7 ]. However, due to the current burden of COVID-19 on public health institutions, one may expect a decrease in vaccination coverage and potential new outbreaks in near future.…”
Section: Introductionmentioning
confidence: 99%
“…Few recent studies have shown a decrease in multiple respiratory agents. [22][23][24][25][26] Interestingly, a case series study, that investigated hospitalisation rates of children under the age of 2 years due to lower respiratory infections, revealed a significant reduction in hospitalisation mainly caused by enveloped viruses. Incidence of unenveloped viruses such as rhinoviruses/enteroviruses did not show such impressive decrease.…”
Section: Discussionmentioning
confidence: 99%
“…The lower basic reproduction number (R 0 ) of influenza20 and IMD21 compared with that of SARS-CoV-2, is a possible explanation for the much stronger impact that those measures had on their transmission. Few recent studies have shown a decrease in multiple respiratory agents 22–26. Interestingly, a case series study, that investigated hospitalisation rates of children under the age of 2 years due to lower respiratory infections, revealed a significant reduction in hospitalisation mainly caused by enveloped viruses.…”
Section: Discussionmentioning
confidence: 99%